2016
DOI: 10.1037/ser0000021
|View full text |Cite|
|
Sign up to set email alerts
|

Women’s veteran identity and utilization of VA health services.

Abstract: Women have participated in the United States military since its founding. However, until the mid-20th century, there had been limited recognition of women as official members of the military, and women remain a statistical minority within military and veteran populations. It is therefore important to better understand women's veteran identity (which we define here as one's self-concept as derived from their veteran status) and associated implications for service use and experiences in the Department of Veteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
2
29
1
Order By: Relevance
“…Previous work has shown that WVs’ discomfort in a male‐dominated environment could lead to nonuse of services, and feeling unwelcome at VA was one of the reasons reported by WVs who had stopped using VA services . Other studies have identified Veteran identity and the perceived fit within VA as influential on the use of VA for women Veterans . More research is needed to understand how to best leverage the different facets of WV identity, as a Veteran and as a woman, to enhance their sense of belonging within VA health care system, and improve their care experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that WVs’ discomfort in a male‐dominated environment could lead to nonuse of services, and feeling unwelcome at VA was one of the reasons reported by WVs who had stopped using VA services . Other studies have identified Veteran identity and the perceived fit within VA as influential on the use of VA for women Veterans . More research is needed to understand how to best leverage the different facets of WV identity, as a Veteran and as a woman, to enhance their sense of belonging within VA health care system, and improve their care experience.…”
Section: Discussionmentioning
confidence: 99%
“…19 Other studies have identified Veteran identity and the perceived fit within VA as influential on the use of VA for women Veterans. 40 More research is needed to understand how to best leverage the different facets of WV identity, as a Veteran and as a woman, to enhance their sense of belonging within VA health care system, and improve their care experience.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the current literature on veteran identity is quite limited (Gade and Wilkins, 2013). Nonetheless, there are a small number of studies on how identification as a veteran can affect preferences for and utilization of medical services (Di Leone,Wang, Kressin, & Vogt, 2016;Locatelli, Turcois, & LaVela, 2014;Matthias et al, 2016). Yet the veteran identity construct remains understudied and requires further articulation and investigation.…”
Section: Civil-military Relationsmentioning
confidence: 99%
“…Di Leone, Wang, Kressin, and Vogt (2016) conceptualized veteran identity as having two dimensions: centrality and positive regard. Centrality refers to how salient a person's veteran status is to their self-concept, whereas positive regard refers to the affective valence a person holds toward their veteran status.…”
Section: Veteran Identitymentioning
confidence: 99%
“…Positive regard for veteran identity was measured using the Positive Regard for Veteran Identity Scale (PRVIS; Di Leone et al, 2016). The original PRVIS had three items and used a five-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree), with a higher score indicating more positive feelings toward the participant's identity as a veteran.…”
Section: Positive Regard For Veteran Identitymentioning
confidence: 99%